Early Secure Attachment as a Protective Factor Against Later Cognitive Decline and Dementia - Walsh, Emilie; Blake, Yvonne; Donati, Alessia; Stoop, Ron; von Gunten, Armin (Frontiers in Aging Neuroscience, 2019)
Although genetic factors contribute to neurodegenerative diseases such as dementia, the etiology of these disorders is complex and incompletely understood. Thus, a growing interest in different approaches including a developmental perspective to these pathologies is gaining momentum. Including environmental factors offers the possibility to enhance our understanding of the etiological factors resulting in the emergence of neurodegenerative processes. Brain, cognitive, and affective reserves can constitute protective factors against the manifestation of symptoms or signs related to cognitive decline in elderly people. These reserves are shaped by the interactions between the person and their environment. Therefore, they are influenced by the quality of the individual’s socio-economic situation, their level of education, the variety and quality of intellectual stimulations and social interactions. Both current and past environment may be of importance. Attachment theory appears to be a valuable candidate to approach the study of the relational early-life environment, as it bears on numerous facets of a person’s development. Besides its established impact on the development of social and affective competencies, recent results highlight that the quality of attachment relations between the child and their caregivers also influences the development of cognitive competencies and, thus, may influence the cognitive reserve in later life. Furthermore, attachment is likely to be involved in neurobiological aspects of brain development as well as in certain epigenetic processes. Through the lens of the attachment theory, this review will attempt to show how the previously mentioned components participate in the development of affective, cognitive and brain reserves, which can in turn act as protective factors against cognitive decline in elderly people.